A method for preparing graphene curved carbon lithium sulfur battery positive electrode material

By using graphene trench carbon structure in the positive electrode material of lithium sulfur battery, loading Li2SO4 and filling it in the multi-layer graphene frame, the problems of poor conductivity, volume expansion and sulfur migration of lithium sulfur batteries are solved, and higher load capacity, conductivity and cyclic stability are achieved.

CN116354339BActive Publication Date: 2025-03-07李海波
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310334091.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-03-16
Filing Date
2023-03-24
Publication Date
2025-03-07
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have problems such as poor conductivity, volume expansion and sulfur migration, resulting in reduced charge and discharge efficiency and short battery life.

Method used

The graphene trocarbon lithium sulfur battery positive electrode material is prepared by calcining and compression by calcining and preparing the graphene trocarbon lithium sulfur battery positive electrode material by calcining and compression.

Benefits of technology

Effectively prevent the volume expansion of lithium sulfur during the circulation process, increase the content of the loaded lithium sulfur, enhance the conductivity and energy density of the battery, reduce the shuttle effect and diffusion of intermediate products, and improve the cycle stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116354339B_ABST
    Figure CN116354339B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a super graphene curved carbon lithium-sulfur battery positive electrode material: (1) evenly dispersing a graphene oxide solution, freeze-drying it, and compressing it to obtain a three-dimensional graphene oxide skeleton; (2) heating chitosan and a foaming agent to obtain foamed carbon, and then ball milling to obtain a curved carbon sheet; (3) soaking the curved carbon sheet in Li 2 SO 4 solution and ultrasonically dispersed to form Li 2 SO 4 Curved carbon sheet aggregate solution; (4) immersing the graphene oxide three-dimensional skeleton into Li 2 SO 4 The curved carbon sheet aggregate rebounds in a solution and then freezes to obtain a precursor; (5) the precursor is calcined in an oxygen-free state to obtain a graphene curved carbon lithium-sulfur battery positive electrode material. The product prepared by this method can effectively enhance the specific capacity and cycle stability of lithium-sulfur batteries, wherein the curved carbon sheet can provide more space for the loading of lithium-sulfur active substances and avoid safety issues caused by battery expansion. This method is simple to prepare and is not affected by the size of the raw materials, and can meet the requirements of industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material chemistry, and in particular relates to a method for preparing a super graphene curved carbon lithium-sulfur battery positive electrode material. Background Art

[0002] Lithium-sulfur battery is a new type of high energy density battery, which is developed on the basis of lithium battery by replacing the positive electrode material on the lithium electrode with sulfur as the positive electrode material. Compared with traditional lithium batteries, lithium-sulfur batteries have many excellent properties and have good application prospects in many fields.

[0003] The advantages of lithium-sulfur batteries are as follows: 1. High specific capacity: Its specific capacity is as high as 1675mAh / g, which is much higher than the capacity of lithium cobalt oxide batteries widely used in business (<150mAh / g). It can provide more power and is suitable for equipment that needs to work for a long time. 2. Low cost: The cost of lithium-sulfur batteries is lower than that of lithium batteries, which is more suitable for mass production. Moreover, most of the materials used for production are natural substances, and there is no problem of price fluctuations. 3. Good safety: Lithium-sulfur batteries are safer than traditional lithium batteries, with low toxicity and can be recycled.

[0004] Although lithium-sulfur batteries have many excellent properties, they still have some disadvantages: 1. Volume expansion: Lithium-sulfur batteries will experience a large volume expansion when charged, which will have a great impact on the battery life and also affect the safety of the battery. 2. Poor conductivity: The poor conductivity of lithium-sulfur batteries will lead to lower charging and discharging efficiency, thereby reducing the actual efficiency of the battery. 3. Poor sulfur mobility: The poor mobility of sulfur will lead to lower charging efficiency and affect the efficiency of the battery. In summary, the shortcomings of lithium-sulfur batteries are mainly concentrated in poor conductivity, volume expansion and other aspects.

[0005] Carbon or graphene can solve the shortcomings of lithium-sulfur batteries. Carbon or graphene has high conductivity, which can improve the conductivity of the battery. By constructing a special structure, it can reduce volume expansion and improve the safety of the battery. In addition, carbon or graphene also has good thermal stability, which can effectively improve the stability of the charge and discharge cycle. However, the current method of adding carbon or graphene is difficult to provide enough space to increase the loading amount of sulfur or its related active substances, reduce a series of loss attenuation caused by battery volume expansion, and cannot be mass-produced due to low product quality or inability to guarantee the yield rate. Summary of the invention

[0006] In view of the poor conductivity and expansion problems of lithium-sulfur batteries in the prior art and in order to further improve the battery specific capacity, the present invention provides a method for preparing a super graphene curved carbon lithium-sulfur battery positive electrode, which is simple and suitable for industrial application.

[0007] To achieve the above purpose, the present invention adopts the following technical solution.

[0008] A method for preparing a graphene curved carbon lithium sulfur battery positive electrode material comprises the following steps:

[0009] (1) evenly dispersing the graphene oxide solution and freeze-drying it, and then compressing it to obtain a three-dimensional graphene oxide skeleton;

[0010] (2) mixing chitosan and a foaming agent uniformly, heating to obtain foamed carbon, and then ball milling to obtain a curved carbon sheet;

[0011] (3) immersing the curved carbon sheet in a Li2SO4 solution and ultrasonically dispersing the solution to form a Li2SO4 curved carbon sheet aggregate solution;

[0012] (4) immersing the graphene oxide three-dimensional skeleton into a Li2SO4 curved carbon sheet aggregate solution for rebound, and then freezing to obtain a precursor;

[0013] (5) calcining the precursor in an oxygen-free environment to obtain a graphene curved carbon lithium-sulfur battery positive electrode material.

[0014] In step (1), the concentration of the graphene oxide solution is 0.5 g / L-30 g / L; and the compression ratio is 0%-96%.

[0015] In step (2), the foaming agent is selected from carbonic acid, ammonium carbonate or ammonium chloride. Preferably, the mass ratio of chitosan to the foaming agent is 50 g / kg-8000 g / kg (1:20-8:1).

[0016] In step (2), the heating temperature and time can be controlled according to the yield, porosity and pore size of the foamed carbon; a wide temperature range can be selected, such as 140°C-990°C; by testing the performance of the foamed carbon obtained at different temperatures, it was found that when the temperature is low, the curved carbon sheet obtained has a stronger ability to adsorb Li2SO4, which is conducive to self-assembly, but its thickness is thicker, which will affect the Li2SO4 loading; when the temperature is high, the curved carbon sheet obtained is thinner, but the adsorption self-assembly ability will be weakened; therefore, in order to facilitate subsequent operations and the overall performance of the positive electrode material, the preferred temperature is 150°C-800°C; by measuring the electrochemical properties of the positive electrode material assembled battery prepared from the foamed carbon obtained at different temperatures, the more preferred temperature is 220°C-480°C.

[0017] In step (2), the size of the curved carbon sheet is 0.01 μm-10 μm.

[0018] In step (3), the mass ratio of the curved carbon sheet to Li2SO4 is 0.001 g / kg-200 g / kg (1:1×10 6 -1:5).

[0019] In step (3), the Li2SO4 solution is a saturated solution.

[0020] In step (4), the material rebounds to a natural state. Preferably, the rebound time is no more than 5 hours.

[0021] In step (4), the mass ratio of the graphene oxide three-dimensional skeleton to the Li2SO4 curved carbon sheet aggregate is 0.0001g / kg-50g / kg (1:1×10 6 -1:20).

[0022] In step (5), the temperature is preheated to no higher than 110°C before calcination; the calcination temperature is 500°C-900°C. Preferably, the calcination temperature is 650°C-770°C; and the heating rate of calcination is 0.1°C / min-10°C / min.

[0023] A graphene curved carbon lithium-sulfur battery positive electrode material obtained by the above preparation method and a lithium-sulfur battery prepared therefrom.

[0024] The present invention has the following advantages:

[0025] The present invention discloses a method for preparing a graphene curved carbon lithium-sulfur battery positive electrode material. The method comprises the following steps: constructing a curved carbon sheet to load Li2SO4 and filling it in a graphene multilayer skeleton, and then calcining and compressing the curved carbon lithium-sulfur battery positive electrode material. The lithium-sulfur active material in the positive electrode material is Li2S. With the help of the three-dimensional space of the curved carbon sheet, the positive electrode material can effectively prevent the volume expansion of lithium-sulfur during the cycle from causing deformation and damage to the battery, and the three-dimensional space formed by the curved carbon sheet has a higher space utilization rate than other methods (such as adding porous carbon, carbon nanotubes, etc.), so the content of loaded lithium-sulfur is also higher; and the diffusion of intermediate polysulfide can be reduced, thereby reducing battery performance. In addition, the curved carbon sheet can significantly increase the conductivity and improve the energy density of the material. The graphene multilayer structure is used to reduce the shuttle effect. The method is not limited by the size of the raw materials, can be produced on a large scale, and meets the needs of industrialization.

[0026] The product prepared by this method can effectively enhance the strength of lithium-sulfur batteries, and use the multilayer structure of graphene to reduce the shuttle effect; and compared with porous carbon, carbon nanotubes and other carbon materials, the curved carbon sheet can provide more space for the loading of lithium-sulfur active substances, while avoiding safety problems caused by battery expansion. In addition, carbon materials are easy to conduct electricity, which improves battery efficiency. At the same time, graphene materials are resistant to high temperatures, avoiding safety hazards caused by high-speed charging and discharging. This method is simple to prepare and is not affected by the size of raw materials. It can meet the requirements of large-scale industrial production and the size of the prepared finished product can be as large as 10m×10m. The initial specific capacity of the graphene curved carbon lithium-sulfur battery is about 900mAH / g Li2S for the positive electrode of the battery, and it can still guarantee more than 90% after 300 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the preparation process of graphene / curved carbon lithium-sulfur battery positive electrode materials. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with embodiments and drawings, but the present invention is not limited by the following embodiments.

[0029] Example 1 Preparation of graphene curved carbon lithium sulfur battery positive electrode material

[0030] (1) evenly dispersing a 15 g / L high concentration graphene oxide solution and rapidly freeze-drying it, and after freeze-drying, compressing it by 60% to form a three-dimensional graphene oxide skeleton;

[0031] (2) 4 g / L chitosan solution and 2 g / L carbonic acid solution were mixed evenly in a mold according to the mass ratio of chitosan to carbonic acid of 2:1, and heated to 220° C. in a muffle furnace to foam and carbonize the mixture, and the foamed carbon was moved into a ball mill for ball milling for 60 min, and passed through a 325-mesh sieve, and the sieve residue was taken, i.e., a micron-grade curved carbon sheet;

[0032] (3) immersing the curved carbon sheet in a saturated Li2SO4 solution, so that the mass ratio of the curved carbon sheet to Li2SO4 is 1:500, and ultrasonically dispersing it to make it self-assembled to form a Li2SO4 curved carbon sheet aggregate solution;

[0033] (4) rapidly adding the graphene oxide three-dimensional skeleton to the Li2SO4 curved carbon sheet aggregate solution at a mass ratio of the three-dimensional skeleton to the aggregate of 1:1200, so that it can fully absorb and rebound; and rapidly freezing with liquid nitrogen after a rebound time of 2 hours to obtain a precursor;

[0034] (5) The temperature of the muffle furnace is preheated to 110°C, and then the precursor is transferred to the muffle furnace for calcination. The temperature is gradually increased to 670°C at a rate of 2°C / min under helium protection.

[0035] After the heating is finished, it is taken out and compressed to 95% of its original volume to prepare the graphene curved carbon lithium sulfur battery positive electrode. After assembling into a full battery, the initial specific capacity is 920.3mAH / gLi2S by electrochemical method, and it can still guarantee 91% after 300 cycles (see Table 1 for details). And its energy density can reach 1600Wh / kg, which is 7-8 times the energy density of the existing industrially produced ternary lithium battery (about 200Wh / kg).

[0036] Example 2 Preparation of graphene curved carbon lithium sulfur battery positive electrode material

[0037] (1) evenly dispersing a 0.5 g / L high concentration graphene oxide solution and rapidly freeze-drying it, and after freeze-drying, compressing it by 70% to form a three-dimensional graphene oxide skeleton;

[0038] (2) 4 g / L chitosan solution and 2 g / L ammonium carbonate solution were mixed evenly in a mold according to the mass ratio of chitosan to ammonium carbonate of 1.2:1, and heated to 200°C in a muffle furnace to foam and carbonize the mixture. The foamed carbon was moved into a ball mill for ball milling for 60 min, and passed through a 1000 mesh sieve to obtain the sieve residue, i.e., a micron-grade curved carbon sheet;

[0039] (3) immersing the curved carbon sheet in a saturated Li2SO4 solution, so that the mass ratio of the curved carbon sheet to Li2SO4 is 1:1000, and uniformly dispersing it by ultrasonication to make it self-assemble to form a Li2SO4 curved carbon sheet aggregate solution;

[0040] (4) rapidly adding the graphene oxide three-dimensional skeleton to the Li2SO4 curved carbon sheet aggregate solution at a mass ratio of the three-dimensional skeleton to the aggregate of 1:100, so that it can be fully absorbed and rebound; after a rebound time of 2 hours, it is rapidly frozen with liquid nitrogen to obtain a precursor;

[0041] (5) The temperature of the muffle furnace was preheated to 110 °C, and then the precursor was transferred to the muffle furnace for calcination, and the temperature was gradually increased to 720 °C at a rate of 5 °C / min under an argon atmosphere.

[0042] After the heating is completed, it is taken out and compressed to 95% of its original volume to prepare the graphene curved carbon silicon sulfur lithium battery positive electrode. After assembling into a full battery, the initial specific capacity is 870.0mAH / gLi2S by electrochemical method, and it can still maintain 92% after 300 cycles (see Table 1 for details).

[0043] Example 3 Preparation of graphene curved carbon lithium sulfur battery positive electrode material

[0044] (1) evenly dispersing a 30 g / L high concentration graphene oxide solution and rapidly freeze-drying it, and compressing it by 96% after freeze-drying to form a three-dimensional graphene oxide skeleton;

[0045] (2) 1 g / L chitosan solution and 2 g / L ammonium chloride solution were mixed evenly in a mold according to a mass ratio of chitosan to ammonium chloride of 1:20, and the mixture was placed in a muffle furnace protected by nitrogen and heated to 460° C. to foam and carbonize the mixture, and the foamed carbon was moved into a ball mill for ball milling for 60 min, and passed through a 10000 mesh sieve, and the sieve residue was taken, i.e., a micron-grade curved carbon sheet;

[0046] (3) immersing the curved carbon sheet in a saturated Li2SO4 solution, so that the mass ratio of the curved carbon sheet to Li2SO4 is 1:5, and ultrasonically dispersing it evenly to make it self-assemble to form a Li2SO4 curved carbon sheet aggregate solution;

[0047] (4) rapidly adding the graphene oxide three-dimensional skeleton to the Li2SO4 curved carbon sheet aggregate solution at a mass ratio of the three-dimensional skeleton to the aggregate of 1:20, so that it can be fully absorbed and rebound; after the rebound time of 4 hours, it is rapidly frozen with liquid nitrogen to obtain a precursor;

[0048] (5) The temperature of the muffle furnace was preheated to 80 °C, and then the precursor was transferred to the muffle furnace for calcination, and the temperature was gradually increased to 900 °C at a rate of 10 °C / min under an argon atmosphere.

[0049] After the heating is completed, it is taken out and compressed to 95% of its original volume to prepare the graphene curved carbon silicon sulfur lithium battery positive electrode. After assembling into a full battery, the initial specific capacity is 1061.2mAH / gLi2S by electrochemical method, and it can still maintain 86% after 300 cycles (see Table 1 for details).

[0050] Example 4 Preparation of graphene curved carbon lithium sulfur battery positive electrode material

[0051] (1) evenly dispersing a 30 g / L high concentration graphene oxide solution and rapidly freeze-drying it, and compressing it by 96% after freeze-drying to form a three-dimensional graphene oxide skeleton;

[0052] (2) 1 g / L chitosan solution and 2 g / L carbonic acid solution were mixed evenly in a mold according to the mass ratio of chitosan to carbonic acid of 1:4, and the mixture was placed in a muffle furnace protected by nitrogen and heated to 380°C to foam and carbonize the mixture. The foamed carbon was moved into a ball mill for ball milling for 60 min, and passed through a 10000 mesh sieve, and the sieve residue was taken, i.e., a micron-grade curved carbon sheet;

[0053] (3) immersing the curved carbon sheet in a saturated Li2SO4 solution, so that the mass ratio of the curved carbon sheet to Li2SO4 is 1:5, and ultrasonically dispersing it evenly to make it self-assemble to form a Li2SO4 curved carbon sheet aggregate solution;

[0054] (4) rapidly adding the graphene oxide three-dimensional skeleton to the Li2SO4 curved carbon sheet aggregate solution at a mass ratio of the three-dimensional skeleton to the aggregate of 1:300, so that it can be fully absorbed and rebound; after the rebound time of 5 hours, it is rapidly frozen with liquid nitrogen to obtain a precursor;

[0055] (5) The temperature of the muffle furnace was preheated to 100 °C, and then the precursor was transferred to the muffle furnace for calcination, and the temperature was gradually increased to 770 °C at a rate of 5 °C / min under an argon atmosphere.

[0056] After the heating is completed, it is taken out and compressed to 95% of its original volume to prepare the graphene curved carbon silicon sulfur lithium battery positive electrode. After assembling into a full battery, the initial specific capacity is 1114.8mAH / gLi2S by electrochemical method, and it can still maintain 92% after 300 cycles (see Table 1 for details).

[0057] Comparative Example 1 Preparation of graphene oxide-porous carbon / sulfur composite material

[0058] Graphene oxide-porous carbon / sulfur composite materials were prepared according to the method in "Preparation of high-porosity graphene oxide-porous carbon composite materials and their application in lithium-sulfur batteries" (Chen Xingbu, 2019):

[0059] (1) Weigh 15g of sodium chloride and dissolve it in 400mL of deionized water, then add 50mL of graphene oxide dispersion (5.0mg / mL) and 5mg of glucose to the sodium chloride solution. Then, ultrasonicate the mixed solution for 5min, with each cycle on for 3s and off for 2s, and the power ratio is 60%, so that the mixed solution is fully mixed. Then, freeze-dry the mixed solution for 36h. After powder pressing, the mixture is placed in a quartz tube furnace and calcined under the protection of an argon atmosphere (200mL / min) to carbonize the glucose and generate porous carbon in situ. In the tube furnace, the sample is first heated from room temperature to 600℃ for 1h, and then calcined at 600℃ for 30min. Finally, the mixture is immersed in deionized water to leach out the sodium chloride, and then the solution is filtered to remove the sodium chloride. The resulting mixture is freeze-dried again to finally obtain graphene oxide-porous carbon (GO-PC);

[0060] (2) GO-PC composite material powder and nano-sized sulfur (S) powder were weighed in a mass ratio of 1:3 respectively. After grinding and mixing for 20 minutes, the mixture was put into a small quartz cup and placed in a quartz tube furnace. It was annealed at 150°C for 12 hours to allow the nano-sulfur particles to penetrate into the interior of the GO-PC composite material, and finally a graphene oxide-porous carbon / sulfur (GO-PC / S) composite material was obtained.

[0061] Application Example 1 Application of graphene curved carbon lithium sulfur battery positive electrode material in lithium sulfur battery

[0062] Assemble the battery according to the method in "Preparation of high-porosity graphene oxide-porous carbon composite materials and their application in lithium-sulfur batteries" (Chen Xingbu, 2019):

[0063] (1) Weighing the composite materials in Examples 1 to 3 or Comparative Example 1 and the binder polyvinylidene fluoride in a mass ratio of 8:1, dispersing them in N-methyl-pyrrolidone, stirring and mixing to form a slurry, coating the slurry on an aluminum foil and drying to obtain an electrode sheet;

[0064] (2) A CR2025 battery shell was used, a Celgard2325 porous polyolefin diaphragm was used as the diaphragm, a 1.0M LiTFSI lithium-sulfur battery electrolyte (DOL:DME=1:1 Vol%; 1.0% LiNO3) was used as the electrolyte, the metal lithium sheet was used as the negative electrode, and the electrode sheet prepared in step (1) was used as the positive electrode. During the battery assembly process, 10 μL of lithium-sulfur battery electrolyte was added, and a nickel foam sheet was placed between the lithium negative electrode and the negative electrode battery shell. After pressing, sealing and drying, the battery assembly was completed.

[0065] The above-mentioned different batteries were subjected to electrochemical performance tests: the cyclic voltammetry test used a scan rate of 0.1 mV / S and a potential range of 1.5 V-2.8 V. The batteries were subjected to constant current charge and discharge tests at different current densities, where the current density is expressed as a multiple (C), 1 C = 1675 mA / g.

[0066] The measurement results of the above-mentioned battery are shown in Table 1: During the first discharge, the graphene / curved carbon lithium-sulfur battery has a higher specific capacity, and the battery can still maintain a higher specific capacity after 300 cycles of charge and discharge. Compared with the porous carbon in Comparative Example 1, the space utilization rate of the curved carbon sheet is higher. Since the curved carbon sheet can form more voids, and the curved carbon sheet is different from the porous carbon and has an open structure, its interface resistance is small, and the active material is easy to diffuse and fill, so the content of the loaded sulfur active material is higher; in addition, when the graphene layer is compressed, the curved carbon sheet will be effectively encapsulated to prevent the diffusion of polysulfide, the intermediate product of the active material, and obtain higher cycle efficiency.

[0067] Table 1 Electrochemical properties of different cathode materials

[0068]

Claims

1. A method for preparing a graphene curved carbon lithium sulfur battery positive electrode material, characterized in that: The following steps are involved: (1) The graphene oxide solution is evenly dispersed and freeze-dried, and then compressed to obtain a three-dimensional graphene oxide skeleton; (2) mixing chitosan and a foaming agent uniformly, heating to obtain foamed carbon, and then ball milling to obtain a curved carbon sheet; (3) immersing the curved carbon sheet in a Li2SO4 solution and ultrasonically dispersing it to form a Li2SO4 curved carbon sheet aggregate solution; (4) Immersing the graphene oxide three-dimensional skeleton in a Li2SO4 curved carbon sheet aggregate solution to rebound, and then freezing to obtain a precursor; (5) Calcine the precursor in an oxygen-free environment to obtain graphene curved carbon lithium-sulfur battery positive electrode material.

2. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the graphene oxide solution is 0.5 g / L-30 g / L; and the compression ratio is 0%-96%.

3. The preparation method according to claim 1, characterized in that: In step (2), the foaming agent is selected from carbonic acid, ammonium carbonate or ammonium chloride; the mass ratio of chitosan to the foaming agent is 50g / kg-8000g / kg.

4. The preparation method according to claim 1, characterized in that: In step (2), the heating temperature is 140°C-990°C; The size of the curved carbon sheet is 0.01μm-10μm.

5. The preparation method according to claim 1, characterized in that: In step (2), the heating temperature is 150°C-800°C.

6. The preparation method according to claim 1, characterized in that: In step (2), the heating temperature is 220°C-480°C.

7. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the curved carbon sheet to Li2SO4 is 0.001g / kg-200g / kg.

8. The preparation method according to claim 1, characterized in that: In step (3), the Li2SO4 solution is a saturated solution.

9. The preparation method according to claim 1, characterized in that: In step (4), the material rebounds to a natural state.

10. The preparation method according to claim 1, characterized in that: In step (4), the rebound time is no more than 5 hours.

11. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the graphene oxide three-dimensional skeleton to the Li2SO4 curved carbon sheet aggregate is 0.0001g / kg-50g / kg.

12. The preparation method according to claim 1, characterized in that: In step (5), the calcination temperature is preheated to no more than 110°C before calcination; the calcination temperature is 500°C-900°C.

13. The preparation method according to claim 1, characterized in that: In step (5), the heating rate of calcination is 0.1°C / min-10°C / min.

14. A graphene curved carbon lithium sulfur battery positive electrode material obtained by any preparation method according to claims 1-13.

15. A lithium-sulfur battery prepared from the graphene curved carbon lithium-sulfur battery positive electrode material as claimed in claim 14.

Citation Information

Patent Citations

  • Three-dimensional porous graphene-supported carbon-coated lithium sulfide cathode material as well as preparation method and application thereof

    CN105406034A

  • Method for preparing lithium carbide / lithium sulfide composite anode material of lithium-sulfur battery by performing carbon thermal reduction on lithium sulfate

    CN106229487A